A Novel Ensembling Technique For Crop Recommendation System Using Machine Learning - Dr.S.Rama krishna, K.Amrutha (International Journal of Advanced Science and Technology, 2020)
In agriculture, most of the losses occur due to incorrect selection of crops that would be suitable for that particular land. In some cases, though they have selected based on soil, there may be some situations where it would fail due to less demand for that product in the market. In this paper, we propose an ensemble model to help the farmers. The ensemble model proposed having the individual base learners such as ANN, Random Forest, SVM, and K.N.N